Consumable texts in contemporary India : uncultured books and bibliographical sociology - Gupta, Suman, 1966- (Houndsmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2015)
"This book examines five areas of English-language publications in India: Indian 'commercial fiction' in English; English translations of Indian vernacular pulp fiction; Hitler's Mein Kampf (which commands a significant market in India and globally); Group Discussion guidebooks; and government 'value education' texts (policy statements, textbooks and related). These kinds of publications are generally neglected by academic researchers, which is itself a matter of interest. Conceptualizing his approach as bibliographical sociology, the author explores the presence of these books in the contemporary Indian context - their productions, circulations and readerships - to understand current social trends. The themes that emerge include perceptions of youth, concerns about education, the status of the English language, the book publishing industry, the relationship between public and private sectors, the drives of global and local forces, and tensions amidst social strata"--
Machine generated contents note: Acknowledgements -- Keywords and Preliminaries -- Indian Commercial Fiction in English -- Indian Vernacular Pulp Fiction in English Translation -- On the Indian Readers of Hitler's Mein Kampf -- Framing Group Discussion Guidebooks -- Low-End Group Discussion Guidebooks and Kunjis -- Approaching Public Sector 'Value Education' Publications -- Mapping Public Sector 'Value Education' Publications -- Rules of Bibliographical Sociology's Method -- Bibliography.
Includes bibliographical references (pages 180-200) and index.
Keywords: Books and reading -- India -- Sociological aspects; English imprints -- Publishing -- India; Popular literature -- Publishing -- India; LITERARY CRITICISM / General; LITERARY CRITICISM / Asian / Indic; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Ethnic Studies / General; SOCIAL SCIENCE / Sociology / General